2010
DOI: 10.1210/en.2010-1197
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Androgen Receptors in Target Musculature Confers Androgen Sensitivity to Motoneuron Dendrites

Abstract: The dendritic arbors of spinal motoneurons are dynamically regulated by a variety of factors, and several lines of evidence indicate that trophic interactions with the target musculature are of central importance. In highly androgen-sensitive motoneuron populations, androgens are thought to regulate motoneuron dendrites through their action at the receptor-enriched target musculature. Using rats transgenically modified to overexpress androgen receptor (AR) in skeletal muscle, we directly tested the hypothesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 83 publications
1
30
0
Order By: Relevance
“…Thus, treatment with testosterone might have supported muscle protein synthesis and decreased protein degradation, and the resultant decrease in protein turnover could have prevented muscle atrophy. However, by using hormone treatments identical to that used in the current study, we have previously demonstrated that the weight of the quadriceps musculature is unaffected in either male (Little et al, 2009; Verhovshek et al, 2010; Huguenard et al, 2011) or female rats (Wilson et al, 2009) by treatment with testosterone.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, treatment with testosterone might have supported muscle protein synthesis and decreased protein degradation, and the resultant decrease in protein turnover could have prevented muscle atrophy. However, by using hormone treatments identical to that used in the current study, we have previously demonstrated that the weight of the quadriceps musculature is unaffected in either male (Little et al, 2009; Verhovshek et al, 2010; Huguenard et al, 2011) or female rats (Wilson et al, 2009) by treatment with testosterone.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, overexpression of wild-type AR in muscle replicates polyQ disease in mouse models of SBMA, 33, 34 suggesting that an expanded polyQ tract is not the only determining factor, and expression levels of specific proteins and unique cellular contexts may also be important factors of toxicity. Our finding that high levels of wild-type AR induced by differentiation and/or DHT treatment in mouse ESCs mimic the effects of expanded polyQ AR raises a number of intriguing open questions; for instance, the issues of whether the pluripotency and differentiation of ESCs is affected by DHT treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This difference in muscle androgen receptor density appears to confer androgen sensitivity on motoneuron morphology. Unlike SNB motoneurons, the morphology of quadriceps motoneurons is normally unaffected by androgen manipulation (Huguenard et al, 2011). As described above, BDNF and trkB protein in quadriceps motoneurons decrease after castration, and the lack of a concomitant decrease in dendritic length suggests that BDNF signaling does not promote dendritic growth in this system.…”
Section: Somatic Motor Systemsmentioning
confidence: 99%
“…As described above, BDNF and trkB protein in quadriceps motoneurons decrease after castration, and the lack of a concomitant decrease in dendritic length suggests that BDNF signaling does not promote dendritic growth in this system. However, androgen sensitivity can be induced in quadriceps motoneuron dendrites by increasing androgen receptor expression in the target musculature of transgenic rats (Huguenard et al, 2011). It would be interesting to examine if the pattern of changes in BDNF levels in response to androgen manipulations in the quadriceps system of androgen receptor overexpressing transgenic rats mimics that seen in the normally androgen-sensitive SNB neuromuscular system.…”
Section: Somatic Motor Systemsmentioning
confidence: 99%